Diversity of the bacterial and viral communities in the tropical horse tick, Dermacentor nitens, in Colombia - Holguin Rocha, Andres Felipe (Kansas State University, 2023)
Ticks are obligatory hematophagous ectoparasites that can transmit pathogens among various vertebrates, including humans. The presence or absence of pathogenic microorganisms is highly variable in ticks, as is the diversity in the composition of their microbial communities, but the factors driving this diversity have not been explored. The tropical horse tick, Dermacentor nitens, is distributed throughout the Americas, and it is recognized as a natural vector of Babesia caballi and Theileria equi, the causal agents of equine piroplasmosis. We characterized the bacterial and viral communities associated with partially fed D. nitens females collected by a passive survey on horses from field sites representing three distinct geographical areas in Colombia, Bolivar, Antioquia, and Cordoba. RNA-seq and sequencing of the V3 and V4 hypervariable regions of the 16S rRNA gene were performed using the Illumina-Miseq platform. A total of 356 operational taxonomic units (OTUs) were identified, in which the presumed endosymbiotic Francisellaceae/Francisella spp. dominated. Differences in the relative abundance of the microbial composition among different regions were found independent of the presence of Francisella-Like Endosymbiont (FLE). The most prevalent bacteria in different regions were; Corynebacterium in Bolivar, Staphylococcus in Antioquia, and Pseudomonas in Cordoba. Rickettsia-like endosymbionts, the main etiological agents of rickettsioses in Colombia, were detected in the Cordoba samples. Metatransctiptomics revealed 13 abundant contigs presenting FLE genes with regional differences. In addition, nine contigs corresponding to six different viruses, in three viral families were also identified, including Chuviridae, Rhabdoviridae, and Flaviviridae. These findings enhance our understanding of the diversity of microbial communities in ticks and may be used to make regional distinctions among the ticks by their bacterial and viral compositions.
Keywords: Next-generation sequencing; Metatranscriptomics; 16S rRNA; RNA-seq; Francisella-like endosymbiont